Remittances and Informal Work - Artjoms Ivlevs (Institute for the Study of Labor (IZA), 2016)
This paper studies the effects of remittances on informal employment in the migrants' countries of origin, looking both at the remittance-receiving and non-migrant households. Using data from the Social Exclusion Survey, conducted in six transition economies in 2009, I find that receiving remittances increases the likelihood of working informally. At the regional level, high prevalence of remittances is associated with a higher likelihood of informal work among non-migrant households. Migration and remittances may thus be contributing to informal employment in migration-sending countries.
Keywords: F24; J46; J61; R23; O17; 330; transition economies; non-migrant households; informal work; migration; remittances; two stage residual inclusion